Prader-Willi syndrome patient with atypical phenotypes caused by mosaic deletion in the paternal 15q11-q13 region: a case report - Jinying Wu; Meifang Lei; Xuetao Wang; Nan Liu; Xiaowei Xu; Chunyu Gu; Yuping Yu; Wei Liu (BMC, 2022)
Abstract Background Prader-Willi syndrome (PWS) is a multisystemic complex genetic disorder caused by the loss of paternally expressed genes in the human chromosome region 15q11.2-q13. It is characterized by severe hypotonia and feeding difficulties in early infancy, followed in later infancy or early childhood by excessive eating and gradual development of morbid obesity. Motor milestones and language development are delayed and most patients have intellectual disability. Case presentation Here we describe a rare PWS case caused by mosaic imprinting defect in the region 15q11.2-q13 of paternal origin. The proband was a male child with a clinical presentation of global developmental delay and hypotonia with specific facial features. Karyotype of the child was noted as mosaic: 45XY,der(15)?t(15;21),-21[26]/46,XY[24]. Whole-exome sequencing (WES) identified a deletion of 22.7 Mb in size at chr15q11.2q21.1 region and a deletion of 2.1 Mb in size at chr21q22.3 region. The Methylation-specific multiplex ligation-dependent probe amplification(MS-MLPA) of the 15q11.2-q13 region showed that the loading ratio of methylated alleles was 70% and that of unmethylated alleles was 30%(50% normal), which confirmed that the loss of mosaic imprinted defects in the paternal allele led to the diagnosis of PWS. Conclusions We propose that complete clinical criteria for PWS should not be considered sensitive in diagnosing partial atypical PWS due to mosaic imprinting defects. In contrast, clinical suspicion based on less restrictive criteria followed by multiple techniques is a more powerful approach.